Estimation of photosynthetically available radiation (PAR) from OCEANSAT-I OCM using a simple atmospheric radiative transfer model. Issue 7 (1st October 2015) - Tripathy, Madhumita; Raman, Mini; Chauhan, Prakash
Abstract: Photosynthetically available radiation (PAR) is an important variable for radiation budget, marine and terrestrial ecosystem models. OCEANSAT-1 Ocean Color Monitor (OCM) PAR was estimated using two different methods under both clear and cloudy sky conditions. In the first approach, aerosol optical depth (AOD) and cloud optical depth (COD) were estimated from OCEANSAT-1 OCM TOA (top-of-atmosphere) radiance data on a pixel by pixel basis and PAR was estimated from extraterrestrial solar flux for fifteen spectral bands using a radiative transfer model. The second approach used TOA radiances measured by OCM in the PAR spectral range to compute PAR. This approach also included surface albedo and cloud albedo as inputs. Comparison between OCEANSAT-1 OCM PAR at noon with in situ measured PAR shows that root mean square difference was 5.82% for the method I and 7.24% for the method II in daily time scales. Results indicate that methodology adopted to estimate PAR from OCEANSAT-1 OCM can produce reasonably accurate PAR estimates over the tropical Indian Ocean region. This approach can be extended to OCEANSAT-2 OCM and future OCEANSAT-3 OCM data for operational estimation of PAR for regional marine ecosystem applications.